Examining the impact of carbon constraints on the capital structure of Chinese power enterprises - Han, Ming Xue; Guo, Zi Xin; Dang, Yi Jing; Long, Tang Zhan (Frontiers in Energy Research, 2023)
China's power system will face more constraints of the carbon emission reduction policy under the goal of “double carbon”, it is particularly important to study the impact of carbon constraints on the capital structure of power enterprises. Commencing the viewpoint of static and dynamic, this research regards the implementation of China's carbon pilot policy as a quasi-natural experiment, using DID method, sys-GMM model and some robustness tests to examine how the carbon constraint affects the capital structure of power companies from 2008 to 2020. The empirical results show that the financial leverage is significantly reduced after the implementation of China's carbon pilot policy. Moreover, the mandatory implementation of carbon emission trading mechanism makes heavy emission enterprises such as power enterprises face greater pressure on emission reduction, resulting in an increase in the risk of financial distress, reducing debt financing and equity financing of power enterprises, which promotes enterprises to decrease financial leverage. In addition, the article verifies another possibility, the enhancement of carbon constraints leads to the reduction of carbon-intensive investment rather than the increase of financial distress risk, so as to reduce the asset-liability ratio. However, the coefficient of interactive items is not significant. Further analysis indicates that the decline of financial leverage is unlikely to be caused by changes in investment.